Warm-up stretching exercises and physical performance of youth soccer players - Hernandez-Martinez, Jordan; Ramirez-Campillo, Rodrigo; Vera-Assaoka, Tiago; Castillo-Cerda, María; Carter-Thuillier, Bastian; Herrera-Valenzuela, Tomás; López-Fuenzalida, Antonio; Nobari, Hadi; Valdés-Badilla, Pablo (Frontiers in Physiology, 2023)
This study aims to compare the effects of standard warm-up versus warm-up using stretching exercises on the physical performance of male youth soccer players. Eighty-five male soccer players (age: 10.3 ± 4.3 years; body mass index: 19.8 ± 4.3 kg/m2) were assessed for countermovement jump height (CMJ, cm), 10 m, 20 m and 30 m running sprint speed (s) and ball kicking speed (km/h) for the dominant and non-dominant leg under five (randomized) warm-up conditions. Using 72 h of recovery between conditions, the participants completed a control condition (CC) and four experimental conditions, including static stretching (SSC), dynamic stretching (DSC), ballistic stretching (BSC), and proprioceptive neuromuscular facilitation (PNFC) exercises. All warm-up conditions had a duration of 10 minutes. The main results indicate that no significant differences (p > 0.05) were found between warm-up conditions compared to CC in CMJ (CC = 28.1 ± 4.9; SSC = 28.4 ± 4.9; DSC = 30.9 ± 4.8; BSC = 30.9 ± 5.2; PNFC = 28.4 ± 5.0), 10 m sprint (CC = 2.42 ± 0.4; SSC = 2.50 ± 0.4; DSC = 2.30 ± 0.3; BSC = 2.27 ± 0.3; PNFC = 2.53 ± 0.4), 20 m sprint (CC = 5.42 ± 0.9; SSC = 5.59 ± 0.9; DSC = 5.37 ± 0.9; BSC = 5.40 ± 0.9; PNFC = 5.44 ± 0.9), 30 m sprint (CC = 8.05 ± 1.3; SSC = 8.27 ± 1.3; DSC = 8.01 ± 1.3; BSC = 8.00 ± 1.3; PNFC = 8.12 ± 1.3), ball kicking speed for dominant (CC = 56.2 ± 4.9; SSC = 55.3 ± 5.2; DSC = 56.9 ± 5.8; BSC = 57.3 ± 5.8; PNFC = 55.7 ± 5.2) and non-dominant leg (CC = 52.8 ± 3.4; SSC = 51.8 ± 4.6; DSC = 53.5 ± 5.4; BSC = 53.6 ± 4.9; PNFC = 52.5 ± 4.0). In conclusion, compared to standard warm-up, stretching-based warm-up exerts no effect on male youth soccer players jump height, sprint speed and ball kicking speed.